2001
DOI: 10.1016/s0141-3910(00)00180-4
|View full text |Cite
|
Sign up to set email alerts
|

An XPS investigation of thermal degradation and charring of cross-linked polyisoprene and polychloroprene

Abstract: This paper is NOT THE PUBLISHED VERSION; but the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in th citation below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Figure (A) shows the C concentration in external and bottom residues of pure EP as a function of combustion time. It should be noted that the C concentration increase gradually for external residue from 0 to 250 s and for bottom residue from 0 to 300 s. The early increase of the C concentration of implies that the other elements, probably hydrogen‐rich fragments, are losing from the surface with crosslinking processes in condensed phase caused by the interaction between radical fragments . As shown in Figure (A), from 0 to 250 s, the C concentration in the bottom residue are lower than that in the external residue, which indicates the crosslinking reaction in the bottom are later than that in the external …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Figure (A) shows the C concentration in external and bottom residues of pure EP as a function of combustion time. It should be noted that the C concentration increase gradually for external residue from 0 to 250 s and for bottom residue from 0 to 300 s. The early increase of the C concentration of implies that the other elements, probably hydrogen‐rich fragments, are losing from the surface with crosslinking processes in condensed phase caused by the interaction between radical fragments . As shown in Figure (A), from 0 to 250 s, the C concentration in the bottom residue are lower than that in the external residue, which indicates the crosslinking reaction in the bottom are later than that in the external …”
Section: Resultsmentioning
confidence: 92%
“…The C and O concentrations in the residue obtained for the pure EP and EP/DOPO/OPS are shown in Tables and . The plasmon loss (△ E L ) is defined as the difference between the main peak in C1s spectra and the plasmon peak in C1s spectra. The plasmon loss data of pure EP and EP/DOPO/OPS are summarized in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…However, very little has been reported in the literature about the influence of surface migration of silicone on the flame retardancy of such a system. The present investigation was carried out with the aid of X-ray photoelectron spectroscopy (XPS) 5,6 and rheological measurements, combined with conventional flammability tests (thermal gravimetric analysis (TGA), Limiting Oxygen Index (LOI), cone calorimetry). The information derived from XPS depends closely upon the l (the inelastic mean free path (IMFP), which is an index of how far an electron can travel through a solid before losing energy).…”
Section: Copolymersmentioning
confidence: 99%
“…The research by Wang et al [62,[81][82][83] showed that X-ray photoelectron spectroscopy (XPS) was an effective tool to study the flame retarded mechanism of polymer/clay nanocomposites. The studies indicated that clay degrades into SiO 2 -like substances that migrate to the surface of materials during combustion.…”
Section: Flame Retarded Polymer Nanocomposites 21 Flame Retarded Polmentioning
confidence: 99%